The Influence of Media Treatments on Color Changes, Dimensional Stability, and Cracking Behavior of Bamboo Scrimber - Jingpeng Li; Yuhe Chen; Jun Xu; Danjing Ren; Hui Yu; Fan Guo; Zaixing Wu (International Journal of Polymer Science)
The purpose of this study is to evaluate the influence of media treatments on color changes, dimensional stability, and cracking behavior of bamboo scrimber, which has many applications in construction. The bamboo scrimber specimens comprised bamboo bundles with a low molecular weight phenol formaldehyde resin which were manufactured via a cold-in and cold-out hot-pressing process. Small clear specimens were sampled and treated under ten different conditions: water immersion at 25°C, 63°C, and 100°C; oil immersion at 100°C and 150°C; air drying at 63°C, 100°C, and 150°C; and infrared drying at 100°C and 150°C. Then, tests were conducted to determine the color changes, dimensional stability, and cracking behavior of the bamboo scrimbers. The results showed that the bamboo scrimber specimens became darker after all treatment conditions, especially the oil treatments and infrared drying. The color of the oil-treated bamboo scrimbers was found to be more homogenous than the others. The dimensional stability of the bamboo scrimbers was more or less influenced by the water treatments, air drying, and infrared drying, and the oil-treated bamboo scrimbers were relatively stable. Moreover, during the 4-hour treatments, cracks were found in the bamboo scrimbers after air drying at 150°C or infrared drying at 100°C or 150°C.